Depression and its predictors among people living with HIV/AIDS on antiretroviral therapy - J., Rudramma; Iti, Jannatbi (International Journal Of Community Medicine And Public Health, 2019)
Background: HIV infection is one of the raising public health problems. HIV diagnosis is usually associated with stigma and often results in mental illness among the people infected. Depression is the most common mental illness in HIV patients as found by various studies. Hence the present study aimed to determine the proportion of depression and its socio-demographic and clinical predictors among people living with HIV/AIDS (PLHA). Methods: A hospital based cross sectional study was done among 322 PLHA on Antiretroviral therapy attending ART centre at GIMS Teaching Hospital, Gadag. After taking written informed consent from the patients, a predesigned proforma which included socio-demographic variables, clinical details, and CD-4 count, along with patient health questionnaire (PHQ) 9 was administered to assess depression in PLHA. Results: Out of the 322 people living with HIV/AIDS, 108 (33.5%) had depressed. According to PHQ 9 questionnaire, 19.9% had mild depression, 10.6% moderate depression and 3.1% had moderate severe depression. It was noted that 40.3% of females had depression compared to 24.8% of males. PHLA who were on ART for less than one year had higher proportion of depression (61.1%) compared to those with 5 years duration of ART (28.6%) and it was statistically significant. Conclusions: In the study 33.5% of PHLA had depression. Socio-economic status, gender, duration of ART had significant association with depression whereas age, education, place of residence, CD4 count were not associated with depression. Depression screening among PHLA can be done at regular follows ups at ART centres.